Comparison of atenolol with propranolol in the treatment of angina pectoris with special reference to once daily administration of atenolol. Issue 9 (September 1978) - Jackson, G; Harry, J D; Robinson, C; Kitson, D; Jewitt, D E
Abstract : Fourteen patients with angina pectoris completed a double blind trial of atenolol 25 mg, 50 mg, and 100 mg twice daily and propranolol 80 mg thrice daily. In comparison with placebo, all active treatments significantly reduced anginal attacks, consumption of glyceryl trinitrate, resting and exercise heart rate, resting and exercise systolic blood pressure, and significantly prolonged exercise time. There was no significant difference between the effects of propranolol and atenolol. Nine patients completed a further trial comparing atenolol given once or twice daily. Both regimens were effective and there was no significant difference between the reductions in anginal attacks, glyceryl trinitrate consumption, systolic blood pressure, or heart rate. Twenty-four-hour ambulatory electrocardiograms showed that atenolol consistently reduced heart rate throughout the 24-hour period whether given once or twice daily. Atenolol is a potent antianginal agent which, in most patients, is likely to be effective once daily.